CuI-catalyzed highly regioselective CH functionalization of indoles using indole-3-tosylhydrazones as carbene precursor: An efficient synthesis of 3, 3-bis(indolyl)methane derivatives. Issue 43 (24th October 2019) - Kamboj, Priya; Dutt, Sunil; Chakroborty, Sourav; Tyagi, Vikas
Graphical abstract: Highlights: Synthesis of bis-indole derivatives having no substitution on methylene-bridge. Copper-catalyzed carbene insertion reactions. Highly regioselective C-3 functionalization of indole over the C-1 and N-1 positions. Gram scale synthesis of bis-indole derivatives. Abstract: Herein, we have developed a novel approach for synthesizing symmetrical and unsymmetrical 3, 3-bis(indolyl)methane derivatives via CuI-catalyzed CH functionalization of indole using indole-3-tosylhydrazones as carbene precursor. This procedure works well with different substitutions such as NO2, Br, CH3 and OMe on indole or indole-3-tosylhydrazones and features high regioselectivity for C-3 functionalization over the C-1 and N-1 positions. Further, we have also revealed the feasibility of this protocol in a one-pot fashion starting from indole-3-carboxyaldehyde.